Short-Chain Fatty Acids Stimulate Glucagon-Like Peptide-1 Secretion via the G-Protein–Coupled Receptor FFAR2 - Tolhurst, Gwen (American Diabetes Association, 2012)
Interest in how the gut microbiome can influence the metabolic state of the host has recently heightened. One postulated link is bacterial fermentation of “indigestible” prebiotics to short-chain fatty acids (SCFAs), which in turn modulate the release of gut hormones controlling insulin release and appetite. We show here that SCFAs trigger secretion of the incretin hormone glucagon-like peptide (GLP)-1 from mixed colonic cultures in vitro. Quantitative PCR revealed enriched expression of the SCFA receptors ffar2 (grp43) and ffar3 (gpr41) in GLP-1–secreting L cells, and consistent with the reported coupling of GPR43 to Gq signaling pathways, SCFAs raised cytosolic Ca(2+) in L cells in primary culture. Mice lacking ffar2 or ffar3 exhibited reduced SCFA-triggered GLP-1 secretion in vitro and in vivo and a parallel impairment of glucose tolerance. These results highlight SCFAs and their receptors as potential targets for the treatment of diabetes.